2015
DOI: 10.1590/0074-02760150004
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of a quantitative polymerase chain reaction-based strategy for the detection and quantification of human herpesvirus 6 DNA in patients undergoing allogeneic haematopoietic stem cell transplantation

Abstract: Human herpesvirus 6 (HHV-6) may cause severe complications after haematopoietic stem cell transplantation (HSCT). Monitoring this virus and providing precise, rapid and early diagnosis of related clinical diseases, constitute essential measures to improve outcomes. A prospective survey on the incidence and clinical features of HHV-6 infections after HSCT has not yet been conducted in Brazilian patients and the impact of this infection on HSCT outcome remains unclear. A rapid test based on real-time quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…The thermocycling conditions were as follows: 30 cycles of 95˚C for 5 min, 95˚C for 30 sec, 63˚C for 30 sec and 72˚C for 30 sec. The mRNA expression levels were normalized to GADPH using the 2 -ΔΔCq quantification method as previously described (24).…”
Section: Rna Extraction and Reverse Transcription-quantitative Polymementioning
confidence: 99%
“…The thermocycling conditions were as follows: 30 cycles of 95˚C for 5 min, 95˚C for 30 sec, 63˚C for 30 sec and 72˚C for 30 sec. The mRNA expression levels were normalized to GADPH using the 2 -ΔΔCq quantification method as previously described (24).…”
Section: Rna Extraction and Reverse Transcription-quantitative Polymementioning
confidence: 99%
“…Recent studies have highlighted the importance of human herpesvirus 6 (HHV-6) in driving infection. 4 , 5 Studies have shown that nearly 40% and occasionally up to 70% of HSCT recipients develop HHV-6 infection. 6 , 7 However, the time of onset and the incidence of HHV-6 after CAR T-cell infusion have not been adequately studied.…”
Section: Introductionmentioning
confidence: 99%